Ultra-wideband microstrip folded antenna for wireless LAN, 5G and Internet of Things applications - Utkarsh Pandey; Parulpreet Singh; Raghvendra Singh; Vivek Kumar; Kanad Ray; Saurav Mallik; Haya Mesfer Alshahrani; E. Elshiekh; Mohamed Abbas; Ben Othman Soufiene (Scientific Reports)
Abstract This paper presents an ultra-wideband (UWB) microstrip antenna with a simple structure operating at 2.2–6 GHz bandwidth. The proposed antenna has been demonstrated for its suitability in UWB and multi-band applications, such as wireless local area network (WLAN), Wi-Fi, 5G, Internet of Things (IoT), etc. The antenna is shown to use a simple folded dipole antenna structure demonstrating an omnidirectional radiation pattern of gain 0.8 to 6 dBi throughout the frequency band. The antenna has strong gain at 2.4, 3.5 and 5.5 GHz. The measured results are shown to have a good agreement with the simulated results.